Analisis Kesulitan Dalam Pembelajaran Matematika Pada Siswa Sekolah Dasar Ditinjau Dari Berbagai Faktor - Fuji Amanda; Sahrun Nisa; Ari Suriani (Universitas 45 Surabaya, 2024)
This study aims to understand the nature of the challenges faced by students in the process of learning mathematics at the primary level, the factors that cause such difficulties, and strategies to overcome the problems that arise. The method used in this study was a literature analysis of various reference sources. The data collection tool is through online searches such as online journals, online books, online articles, theses and other sources without conducting field research which is taken via Google Scholar. “The results of data analysis from the research show (1) the characteristics of the difficulties experienced by students in learning mathematics, namely difficulties in understanding mathematical concepts, difficulties understanding visual-spacial objects, difficulties in calculating operations, difficulties in reading and understanding math problems in the form of stories, lack of motivation to learn , lack of teacher activity in creating interesting learning media”. (2) the factors causing these difficulties consist of internal and external factors. (3) efforts that can be implemented to overcome these problems are (1) Using innovative and interesting learning approaches; (2) Utilizing concrete and interactive learning media; (3) Providing appropriate guidance and scaffolding; (4) Identifying and overcoming difficulties individually; (5) Increase students' motivation and interest in learning.